The Influence of Lecture and Question and Answer Methods Assisted by Video Learning Media on Primary School Students' Science Critical Thinking Abilities - Rosa Susila Prestikadini; Erlinda Rahma Dewi (UIN Raden Mas Said Surakarta, 2023)
The ability to think critically is a process of understanding and examining a problem or object by actively considering and evaluating statements and ideas that have meaningful value. This study aims to determine students' critical thinking skills in science subjects after being given treatment by applying lecture and question-and-answer methods with the help of video learning media. This research was conducted at Madrasah Ibtidaiyah Muhammadiyah Klaseman Gatak. The study was conducted in November 2022. The research method used is pre-experimental—data analysis using a paired sample t-test. The instrument used in this study is a critical thinking ability test in the form of a description of 9 questions. Validation in this research instrument is expert validation and empirical validation. Expert validation was given to two expert lecturers, and empirical validation was given to 21 grade IV B MI Muhammadiyah Klaseman students. The study sample was 22 students in class IV A, with a population of 43. The study's results averaged a pretest score of 57.24 while the average posttest score of 63.47 obtained a significant value, 0.069>0.05, so Ho was accepted, and Ha was rejected. It can be concluded that there is no significant influence on the use of lecture and question-and-answer methods with the help of learning media on students' critical thinking skills in grade IV science subjects at Muhammadiyah Islamic Elementary School Klaseman